Distribution and bioaccumulation of prometryn in simulated aquatic ecosystems - Peng, Jiaqi; Fan, Ruiqi; Ren, Yuanyuan; Yang, Yan; Zhang, Xin; Wang, Saisai; Mu, Yingchun; Cheng, Bo (Frontiers in Environmental Science, 2025)
Prometryn is an herbicide widely used in agriculture. Its degradation-resistant properties have raised concerns about its environmental impact on aquatic systems, yet its environmental distribution and bioaccumulation remain to be explored. This research examined the environmental distribution of prometryn within lab-simulated aquatic ecosystems, incorporating water-sediment interactions and bioaccumulation in tilapias (Oreochromis niloticus) and Asian clams (Corbicula fluminea). The research aims to explore the bioaccumulation dynamics of prometryn across both biotic and abiotic components of the ecosystem, providing a comprehensive understanding of its environmental persistence and accumulation in aquatic organisms and sediments. The ecosystems were exposed to a prometryn concentration of 0.50 mg/L for 35 days. During the experiment, significant adsorption and retention of prometryn in the sediment were observed, suggesting that the sediment could be the primary repository. Additionally, tilapias and Asian clams not only served as accumulative pools for prometryn but also influenced its distribution dynamics within the ecosystems. In terms of bioconcentration, the highest bioconcentration factors were observed in the liver of tilapias and the visceral mass of Asian clams, suggesting a strong affinity of prometryn for these tissues. The persistently high levels of prometryn indicate potential risks to aquaculture product safety. The study concludes with a recommendation for ongoing ecological risk assessments, particularly regarding benthic organisms, given the propensity of prometryn to accumulate in sediment within aquaculture systems.